Analysis of the Management of Interest-Free Loans by the National Amil Zakat Agency of Sungai Penuh City for the Development of Micro, Small and Medium Enterprises - Elex Sarmigi; Syukrawati Syukrawati; Azhar Azhar; Desiana Desiana; Dinda Fitria Ramadani (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2023)
This study aims to determine the interest-free loan management system by BAZNAS for MSME business development in the Sungai Penuh City. The subject of this research is the manager and mustahik of BAZNAS Sungai Penuh City. The informants in this study were leaders and mustahik at BAZNAS, the Sungai Penuh City. This study applies a qualitative approach to data collection techniques by conducting interviews. The results of this study found that capital assistance that was loaned without interest by BAZNAS of Sungai Penuh City had not been fully successful. Supporting factors for the application of interest-free loans at BAZNAS Sungai Penuh City are good human resources and good work procedures. While the inhibiting factor is that the borrowers experience problems in repaying. The strategy carried out by BAZNAS Sungai Penuh City is to help the poor, such as assistance that is consumptive or assistance that is productive in nature, the requirements for getting assistance from BAZNAS are first the poor and the poor, some of the main activities at BAZNAS Sungai Penuh City are distribution and utilization.